DAMPAK CUSTOMER RELATIONSHIP MANAGEMENT DAN KEPUASAN PELANGGAN PADA LOYALITAS PELANGGAN DI VIOLETTA GRESIK - AZHARUL ILMI (Jurnal Manajerial, 2018)
Business growth now depends not only on product quality, but also look in terms of quality of service, through the CRM companies can determine the extent of use of CRM in the business world. The purpose of this study to find out is to find out whether the CRM and customer satisfaction affects customer loyalty either simultaneously or partially. Some of the variable as an indicator of CRM and customer satisfaction in this study include management, relationships, affect customer loyalty in Gresik Violetta. The analysis tools is to use multiple linear regression with SPSS trial hypothesis using t test and f test, both at a significant level of 5%. Calculation results show that both variables are included in the analysis together have a significant effect on customer loyalty in Gresik Violetta. This conclusion is based on results that show the value of F count for more than 46.006 3.09 F tables of two variables, it appeared that CRM has a significant influence calculated t value of 4.57 with a significance level of 0.00%. Based on the results of the analysis of customer loyalty in a very dominant Violetta Gresik of CRM, CRM of these two variables should be further enhanced so that consumers understand more CRM and customer satisfaction on customer loyalty.